Extracting hand grasp and motion for intent expression in mid-air shape deformation: A concrete and iterative exploration through a virtual pottery application. (April 2016) - Vinayak,; Ramani, Karthik
Abstract: We describe the iterative design and evaluation of a geometric interaction technique for bare-hand mid-air virtual pottery. We model the shaping of a pot as a gradual and progressive convergence of the pot-profile to the shape of the user׳s hand represented as a point-cloud (PCL). Our pottery-inspired application served as a platform for systematically revealing how users use their hands to express the intent of deformation during a pot shaping process. Our approach involved three stages: (a) clutching by proximal-attraction, (b) shaping by proximal-attraction, and (c) shaping by grasp+motion. The design and implementation of each stage was informed by user evaluations of the previous stage. Our work evidently demonstrates that it is possible to enable users to express their intent for shape deformation without the need for a fixed set of gestures for clutching and deforming a shape. We found that the expressive capability of hand articulation can be effectively harnessed for controllable shaping by organizing the deformation process in broad classes of intended operations such as pulling, pushing, and fairing. After minimal practice with the pottery application, users could figure out their own strategy for reaching, grasping, and deforming the pot. Users particularly enjoyed using day-to-day physical objects as tools for shaping pots. Abstract : Graphical abstract: Grasp detection from Kernel density. Abstract : Highlights: We present iterative algorithm development for mid-air virtual pottery design. We extract grasp and motion using kernel-density of the point-cloud of hands. We use hand grasp and motion for classifying intent towards pot׳s deformation. Users can shape pots with hands as well as physical objects as tools. Evaluation shows increase in controllability in intent expression in pottery.